Contextual Media as a Strategy to Improve Students’ Conceptual Understanding and Learning Independence - Kusumadewi, Tri Cahyani; Muhajir, Muhajir; Huda, Nuril; Hanifah, Yuni (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to assess the effectiveness of contextual learning media in improving the conceptual understanding and independent learning of 5th-grade students at Keleyan 2 Socah Elementary School. The saturation sampling method was used to ensure that the entire population of 50 students from classes V-A and V-B was included in the research sample. A quantitative approach using an evaluative design was employed, including tools such as concept comprehension tests and learning independence questionnaires. Data analysis was conducted using IBM SPSS software, including validity testing, reliability testing, homogeneity testing, normality testing, and independent samples t-tests for hypothesis evaluation. The analysis findings show significant differences in the concept understanding variable, with a significance value of 0.002, which is less than 0.05, and in the learning independence variable, with a significance value of 0.000, also less than 0.05. The results confirm that contextual learning media positively influences elementary school students’ understanding of mathematical ideas and improves their self-directed learning abilities.